THE ROLE OF TEACHER IN IMPROVING THE SOCIAL CARE CHARACTER IN LEARNING CIVICS - Fadil, Khaidir (Department of Research and Community Service at the Ummul Quro Al-Islami Bogor Institute, 2025)
This study aims to find out, what is the role of the teacher in instilling a socially caring character through PKN learning at MIS Miftahul Athfal Tenjolaya. This research is a qualitative research using descriptive methods to determine the teacher's role in instilling a socially caring character through Civics learning at MIS Miftahul Athfal Tenjolaya through Civics Learning. The research subject at the research school was the MIS teacher Miftahul Athfal. This research uses indirect interview method. The primary data source used as the primary information source is the Civics subject teacher. Secondary data in the form of journals and books. Data collection techniques used are observation and interviews. The data analysis technique uses the interaction model analysis technique according to Miles and Huberman, namely data reduction (data reduction), data presentation (data visualization) and drawing conclusions (verification). The results of the study show that the role of Civics teachers at MIS Miftahul Athfal Tenjolaya is in implementing socially caring characters, namely by direct examples and advising students to be polite, help each other, love one another and tolerate differences. in conclusion. One of the implementations of the cultivation of social care character is what is done by teachers at MIS Miftahul Athfal in its implementation The teachers there teach students in their classes to be polite to each other, help each other and tolerate differences both with teachers and with peers either by giving direct examples to their students or through giving advice to student